Reply to: malnutrition in idiopathic pulmonary fibrosis: the great forgotten comorbidity! - Torrisi, Sebastiano Emanuele; Kreuter, Michael (The European respiratory journal, 2019)
The role of malnutrition in IPF remains uncertain and should be considered a consequence of the disease and not a comorbid condition. However, given the high prevalence of malnutrition in IPF its impact on mortality should be further evaluated. http://ow.ly/5CKe30okjma